In-situ Tests and Analysis for Droplet Size Distribution on the Clean Flue of Coal-fired Power Plant. Issue 1 (February 2020) - Li, Zonghui; Cao, Wenguang; Liu, Xiu; Chen, Jun; Duan, Cuijia
Abstract: The clean flue gas after FGD of coal-fired power plant is taken as the analysis object, and the particle size analysis for droplets under complex conditions is studied. Selected 600MW unit is typical enough, the particle size range is mainly between 3 and 20 μm. The test will provide the first-hand data for the removal of fine droplets.